PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN INTERAKTIF BERBASIS WORDWALL TERHADAP MOTIVASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN SOSIOLOGI KELAS X FASE E SMA NEGERI 16 PADANG - Ramadani, Aulia; Faishal Yasin; Yanti Sri Wahyuni (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research aims to analyze the effect of using interactive learning media based on Wordwall on students' learning motivation in Sociology subject at grade X Phase E of SMA Negeri 16 Padang. The study involved 39 students, consisting of 19 male and 20 female students. The research employed a quantitative method with purposive sampling technique. The results indicated a significant effect of Wordwall media on students' learning motivation, with a significance value of 0.010 (p < 0.05). This suggests that the use of interactive learning media positively influences students' motivation in learning Sociology. The findings are expected to contribute to the development of more innovative and effective teaching methods.